MY SAY: Of financial and education system failures - Abd Razak, Dzulkifli (2010)
As leaders in all sectors contemplated what to do next at the recent World Economic Forum in Davos, more US banks were reportedly failing due to the economic crisis and were being seized by the regulators. The number of bank failures this year is expected to peak from last year's figure of 140. That compares with just 25 banks which failed in 2008 and only three in 2007. Collectively, billions have literally been lost over this period.